2012
DOI: 10.1210/en.2012-1469
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Estrogen Regulation of Membrane Progesterone Receptor-β in the Female Rat Brain

Abstract: Although several studies have reported the localization of membrane progesterone (P(4)) receptors (mPR) in various tissues, few have attempted to describe the distribution and regulation of these receptors in the brain. In the present study, we investigated expression of two mPR subtypes, mPRα and mPRβ, within regions of the brain, known to express estradiol (E(2))-dependent [preoptic area (POA) and hypothalamus] and independent (cortex) classical progestin receptors. Saturation binding and Scatchard analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 69 publications
6
52
0
Order By: Relevance
“…By RT-qPCR we Above results agree with other reports in which mPRβ is the predominant mPR in different human and rodent brain regions such as cerebral cortex, cerebellum, pituitary, thalamus, hypothalamus and caudate nucleus [22,43]. In contrast, mPRα is predominantly expressed in human reproductive tissues, though some recent studies have reported its expression in cerebral cortex, hippocampus, thalamus, hypothalamus and cerebellum of rat and mouse [41,44,45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…By RT-qPCR we Above results agree with other reports in which mPRβ is the predominant mPR in different human and rodent brain regions such as cerebral cortex, cerebellum, pituitary, thalamus, hypothalamus and caudate nucleus [22,43]. In contrast, mPRα is predominantly expressed in human reproductive tissues, though some recent studies have reported its expression in cerebral cortex, hippocampus, thalamus, hypothalamus and cerebellum of rat and mouse [41,44,45].…”
Section: Discussionsupporting
confidence: 90%
“…In fact, ERE and PRE have been reported in promoter regions of mPRα, mPRβ and mPRγ of catfish [47]. [43]. Similarly, using quantitative PCR, Inteklofer and Petersen reported an upregulation of mPRβ, but no mPRα mRNA in the anteroventral periventricular nucleus (AVPV), ventromedial nucleus and sexually dimorphic nucleus of the preoptic area after implanted E-containing capsules for a longer than 56-h exposure in female rats, while in the same model, P repressed mPRβ gene expression only in AVPV [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PROG also binds to membrane PROG receptor (mPR)-α and -β [30]. PR-A, PR-B, and mPR-α are expressed in the striatum [31,32], while PR-A, PR-B, and mPR-β have been found in the substantia nigra [33,34,35]. Whereas the mechanisms of PROG action in the striatum have received little attention, PROG is reported to mediate its effect through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…mPRα is also induced by gonadotropins during seatrout oocyte maturation followed by a dramatic decrease in ovulated oocytes (Zhu et al, 2003b). By contrast, mPRβ gene is highly expressed during zebrafish oocyte maturation and the corresponding protein levels were also increased during this process (Hanna and Zhu, 2009 It has been proposed that during fish oocyte maturation mPRα activates a pertussis toxin-sensitive inhibitory G protein (G i ), which in turn inhibits the activity of adenylyl cyclase (AC) to decrease cAMP levels (Thomas, 2012). In contrast to fish models, it has been reported that mPRβ regulates oocytes maturation in pig and Xenopus (Josefsberg Ben-Yehoshua et al, 2007;Qiu et al, 2008), suggesting that oocyte maturation mediated by specific mPRs subtypes is species dependent In fish, PKA activation by cAMP usually results in the inactivation of MAPK signaling and the inhibition of oocyte maturation by downregulating cyclin B levels (black lines).…”
Section: Mprs In Female Reproductive Tissuesmentioning
confidence: 99%